1995
DOI: 10.1105/tpc.7.8.1173
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Activity during Pollen Tube Growth and Reorientation.

Abstract: We have shown previously that the inhibition of pollen tube growth and its subsequent reorientation in Agapanthus umbellatus are preceded by an increase in cytosolic free calcium ([Ca2+]c), suggesting a role for Ca2+ in signaling these processes. In this study, a novel procedure was used to measure Ca2+ channel activity in living pollen tubes subjected to various growth reorienting treatments (electrical fields and ionophoretic microinjection). The method involves adding extracellular Mn2+ to quench the fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
134
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(144 citation statements)
references
References 22 publications
8
134
2
Order By: Relevance
“…Wu, unpublished data). The stretch-activated PM Ca 21 channels have been proposed to be present in pollen and pollen tubes and may function in pollen germination and tube growth (Pierson et al, 1994;Malhó et al, 1995;Malhó and Trewavas, 1996). The features of the stretch-activated Ca 21 channels differ from those of the hyperpolarization-activated Ca 21 channels in pollen and pollen tubes reported in this study.…”
Section: Identification Of Ca 21 Channels In Arabidopsis Pollen Protocontrasting
confidence: 53%
See 2 more Smart Citations
“…Wu, unpublished data). The stretch-activated PM Ca 21 channels have been proposed to be present in pollen and pollen tubes and may function in pollen germination and tube growth (Pierson et al, 1994;Malhó et al, 1995;Malhó and Trewavas, 1996). The features of the stretch-activated Ca 21 channels differ from those of the hyperpolarization-activated Ca 21 channels in pollen and pollen tubes reported in this study.…”
Section: Identification Of Ca 21 Channels In Arabidopsis Pollen Protocontrasting
confidence: 53%
“…These two organic Ca 21 channel blockers are commonly used to block animal Ca 21 channels (Hess, 1990). The findings of this study and of Malhó et al (1995) suggest that different types of Ca 21 channels may exist in pollen and pollen tubes from those in animal cells. In addition, we observed another type of Ca 21 channel, which was stretchactivated and Gd 31 -or La 31 -sensitive, in Arabidopsis and Brassica pollen protoplasts (Y.F.…”
Section: Identification Of Ca 21 Channels In Arabidopsis Pollen Protomentioning
confidence: 72%
See 1 more Smart Citation
“…S4 D and E). We tested this prediction by treating pollen tubes with LaCl 3 , a calcium channel blocker that has been shown to lower cytosolic calcium levels in pollen tubes (32). When treated with 10 M LaCl 3 , the pollen tubes maintained a high level of apical ROP1 activity (Ͼ 1.5) but lost its oscillation (Fig.…”
Section: Simulation and Experimental Validation Of The Effect Of Calcmentioning
confidence: 99%
“…[1][2][3] Early studies were focus on the plasma membrane calcium channel regulation and cytosolic free calcium concentration variation in the pollen tube reason by which was one of the most important second messengers in plants. [3][4][5][6][7] However, reports have also showed that the potassium channels in the pollen tubes were also involved in several important steps of plant sexual reproduction. [8][9][10][11][12][13][14][15][16][17][18][19] Recently, more reports further demonstrated this phenomena.…”
mentioning
confidence: 99%